2019
DOI: 10.1042/ebc20190022
|View full text |Cite
|
Sign up to set email alerts
|

The role of DUBs in the post-translational control of cell migration

Abstract: Cell migration is a multifactorial/multistep process that requires the concerted action of growth and transcriptional factors, motor proteins, extracellular matrix remodeling and proteases. In this review, we focus on the role of transcription factors modulating Epithelial-to-Mesenchymal Transition (EMT-TFs), a fundamental process supporting both physiological and pathological cell migration. These EMT-TFs (Snail1/2, Twist1/2 and Zeb1/2) are labile proteins which should be stabilized to initiate EMT and provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 173 publications
0
6
0
Order By: Relevance
“…The stability of EMT-related transcription factors is essential for initiating cellular EMT. Thus, the deubiquitinases (DUBs) were involved in counteracting polyubiquitination and proteasomal degradation of ZEB1 [40]; these DUBs include USP51, which upregulated ZEB1 and the mesenchymal markers by binding, deubiquitinating, and stabilizing ZEB1 [41]. In addition to DUBs, other factors, such as CSN5, an oncogene involved in various types of cancer, may also interrupt the degradation of ZEB1 by stabilizing ZEB1 by directly interacting with it [42].…”
Section: The Regulation Of Zeb1 Expression and Activitymentioning
confidence: 99%
“…The stability of EMT-related transcription factors is essential for initiating cellular EMT. Thus, the deubiquitinases (DUBs) were involved in counteracting polyubiquitination and proteasomal degradation of ZEB1 [40]; these DUBs include USP51, which upregulated ZEB1 and the mesenchymal markers by binding, deubiquitinating, and stabilizing ZEB1 [41]. In addition to DUBs, other factors, such as CSN5, an oncogene involved in various types of cancer, may also interrupt the degradation of ZEB1 by stabilizing ZEB1 by directly interacting with it [42].…”
Section: The Regulation Of Zeb1 Expression and Activitymentioning
confidence: 99%
“…Acute myeloid leukemia MSCs promoted the mRNA level of Snail1 but inhibited its protein expression; this does not conform to classical EMT regulation. It has been reported that Snail1 protein is unstable and controlled by a specific type of protease 32 . Acute myeloid leukemia MSCs also promoted the mRNA levels of Twist1 and vimentin in K562 cells and HL60 cells, but had the opposite or little effect on relevant protein expressions in K562 cells and HL60 cells, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that Snail1 protein is unstable and controlled by a specific type of protease. 32 Acute myeloid leukemia MSCs also promoted the mRNA levels of Twist1 and vimentin in K562 cells and HL60 cells, but had the opposite or little effect on relevant protein expressions in K562 cells and HL60 cells, respectively. It had been reported that EMT is dynamic and not a binary process, depending on the cell type and tissue type.…”
Section: Discussionmentioning
confidence: 95%
“… 26 More evidence indicates that USP17 subfamily proteins may regulate EMT of various cells by acting on Snail1, Snail2, and Twist1. 27 …”
Section: Discussionmentioning
confidence: 99%